Effectiveness of Differentiated Learning in Natural and Social Science Projects Aspects of Substances and Their Changes in Realizing the Pancasila Student Profile Dimensions of Faith, Devotion to God Almighty and Having Noble Morals - Nur Latifah; Muhammad Syaipul Hayat; Nur Khoiri (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to evaluate the effectiveness of differentiated learning in the Natural and Social Sciences Project (NSS Project)ith a focus on aspects of substances and their changes. The application of this learning model is directed at realizing the Pancasila student profile of the dimensions of faith, devotion to God Almighty, and noble character by emphasizing the moral element towards nature. The research method used was experimentation with a control class and an experimental class. Differentiated learning is applied to the experimental class, while the control class receives conventional learning. Based on the results of the N-gain score test calculation, it shows that the average N-gain score for the experimental class (differentiated learning approach) is 57.1599 or 57.2%, which is in the quite effective category. With a minimum N-Gain value of 29.63% and a maximum of 89.67%. Meanwhile, the average N-Gain score for the control class (conventional learning) was 32.3181 or 32.3%, which was included in the ineffective category. With a minimum N-gain score of 10.875 and a maximum of 54.35%. So it can be concluded that the use of a differentiated learning approach is quite effective in increasing the profile of Pancasila students in the dimensions of faith, devotion to God Almighty and noble moral.